A Crowdsourcing-based Air Pollution Measurement System Using DIY Atomic Force Microscopes (Human Computation, 2016)
Air pollutants have become the major problem of many cities, causing millions of human deaths worldwide every year. Among all the noxious pollutants in air, particles with a diameter of 2.5 micrometers or less (PM2.5) are the most hazardous because they are small enough to penetrate to the lungs and invade the smallest airways. Since the presence of dangerous levels of PM2.5, commonly reported in newspapers and on TV, is intertwined with the global pattern of production and consumption, there is a need for citizen science projects that engage the young generations in efforts toward reducing air pollution as they will become the future leaders of society. With this goal, and to enable the geo-temporal characterization of PM2.5, we present a crowdsourcing-based air pollution measurement system that uses affordable DIY atomic force microscopes to measure and characterize PM2.5, exploiting the power of human computation through an online crowdsourcing platform to study how PM2.5 varies over time and across geographical locations. Our system is intended as both a scientific platform and a teaching tool for children to engage in environmental policy.
Keywords: pollution; pm2.5; atomic force microscopy; crowdsourcing; cyberlab